Simultaneous Quantitation of Eight Coumarins in Radix angelicae dahuricae by Micellar Electrokinetic Capillary Chromatography - Zhu, Hong; Kong, Dezhi; Xu, Huijun; Wang, Na; Zhao, Chengcheng; Liu, Pengwei; Zhang, Lantong (Asian Journal of Chemistry, 2011)
A new simple, rapid, sensitive and accurate quantitative detection method using micellar electrokinetic capillary chromatography for the measurement of eight coumarins levels in Radix angelicae dahuricae is described, namely scopoletin (1), xanthotoxol (2), xanthotoxin (3), bergapten (4), oxypeucedanin (5), imperatorin (6), cnidilin (7) and isoimperatorin (8). Analytes were separated on the buffer solution which contained 10 mM borax, 40 mM sodium dodecyl sulfate and 20 % (v/v) acetonitrile, 22 kV for the separation voltage at 20 ºC. 7 of the 8 coumarins (expect xanthotoxol) were simultaneously quantitated. The recovery of the 7 coumarins was in the range of 92.7-105.6 % with RSD values less than 3.6 %.